Building Competencies for Industry 4.0: Suggestions from Kazakhstan Experience - Anna SHEVYAKOVA; Yelena PETRENKO; Natalia FOMENKO; Eleonora MUNSCH; Nazgul DARIBEKOVA (Communications of International Proceedings, 2023)
The article reveals possible recommendations for action on competency development (with a focus on digital competencies), which are caused by the increasing requirements of Industry 4.0 and the rapid growth of digitalization in the economy. In this context, it is important to prepare staff by raising awareness of the ongoing changes and emerging new requirements for skills and competencies. The article discusses and analyzes the necessary competencies for the successful integration of Kazakh enterprises into Industry 4.0. The article proposes the division of Kazakhstani economic entities into three contact audiences: companies themselves, education `providers and state institutions, and also proposes a draft Checklist for companies to develop competencies for Industry 4.0, which includes recommendations and a description of possible threats and obstacles.
Keywords: Industry 4.0.; digitalization; digital competencies; Kazakhstan